2022
DOI: 10.2174/1381612828666220628123224
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Obesity and Diabetes: Introducing Polyphenols as an Effective Phytomedicine to Combat the Dual Sword Diabesity

Abstract: Obesity-associated diabetes mellitus, a chronic metabolic affliction accounting for 90% of all diabetic patients, has been affecting humanity extremely badly and escalating the risk of developing other serious disorders. It is observed that 0.4 billion people globally have diabetes, whose major cause is obesity. Currently, innumerable synthetic drugs like alogliptin and rosiglitazone are being used to get through diabetes, but they have certain complications, restrictions with severe side effects, and toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 244 publications
0
4
0
Order By: Relevance
“…Thus, reduction of ROS has been proposed as an effective strategy for mitigating inflammation and complications associated with diabetes ( Cheng et al, 2019 ). Several natural antioxidants including polyphenols, have been shown to reduce the risk of T2DM via increasing the antioxidant defense, regulating inflammatory response and decreasing blood glucose and insulin resistance ( Shah et al, 2022 ; Kukavica et al, 2024 ). Therefore, it is in need to further discover high-efficiency, low-toxicity and multi-target antioxidants for diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduction of ROS has been proposed as an effective strategy for mitigating inflammation and complications associated with diabetes ( Cheng et al, 2019 ). Several natural antioxidants including polyphenols, have been shown to reduce the risk of T2DM via increasing the antioxidant defense, regulating inflammatory response and decreasing blood glucose and insulin resistance ( Shah et al, 2022 ; Kukavica et al, 2024 ). Therefore, it is in need to further discover high-efficiency, low-toxicity and multi-target antioxidants for diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that phytochemicals can ameliorate obesity-induced diabetes mellitus in vivo and in vitro [ 28 , 29 ]. In this study, we have demonstrated that phycocyanin can protect against high glucose high fat diet induced diabetes mellitus in mice and can also ameliorate the insulin-resistant effect of SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive accumulation of adipose tissue in the human body, known as obesity, is the strongest risk factor for developing diabetes, namely, type 2 diabetes mellitus (T2DM), which is responsible for 90% of all diabetic patients [ 176 ]. The term diabesity represents this crosstalk between obesity and diabetes sharing inflammatory processes as a hallmark.…”
Section: Significance Of Acns From Plants To Human Health Benefitsmentioning
confidence: 99%